Pengaruh Mobile Banking dan Kepuasan Nasabah Terhadap Loyalitas Nasabah pada PT Bank Sumut Sei Sikambing Medan Sumatera Utara - Nasution, Amrin mulia; Wulandari, Inmas Tri; Nasution, Nur Aisyah; Sihombing, Tohap Parulian (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of mobile banking and customer satisfaction on customer loyalty at PT Bank Sumut KCP Sei Sikambing Medan, North Sumatra. The research approach used is quantitative, which will determine the extent of the influence of independent variables on dependent variables. The population in this study consists of all customers using mobile banking at PT Bank Sumut KCP Sei Sikambing, totaling 600 customers in 2024. The sampling technique used in this study is the Solvin formula, resulting in 86 respondents. Data analysis was conducted using SPSS 27 with multiple linear regression analysis to determine the influence of independent variables on dependent variables. The results of the study indicate that Mobile Banking has a positive and significant effect on customer loyalty. This is evident from the significant value (0.000) < 0.05. The Customer Satisfaction variable has a positive and significant effect on customer loyalty. This is evident from the significant value (0.000) < 0.05, simultaneously indicating that the influence of the independent variables Mobile Banking (X1) and Organizational Culture (X2) together is significant on Customer Loyalty.